Evaluation of the bioactive properties of avenanthramide analogs produced in recombinant yeast. (30th January 2015) - Moglia, Andrea; Goitre, Luca; Gianoglio, Silvia; Baldini, Eva; Trapani, Eliana; Genre, Andrea; Scattina, Antonella; Dondo, Giancarlo; Trabalzini, Lorenza; Beekwilder, Jules; Retta, Saverio Francesco
Abstract Saccharomyces cerevisiae has been proven to be a valuable tool for the expression of plant metabolic pathways. By engineering a S. cerevisiae strain with two plant genes (4cl‐2 from tobacco and hct from globe artichoke) we previously set up a system for the production of two novel phenolic compounds, N‐(E)‐p‐coumaroyl‐3‐hydroxyanthranilic acid (Yeast avenanthramide I, Yav I) and N‐(E)‐caffeoyl‐3‐hydroxyanthranilic acid (Yeast avenanthramide II, Yav II). These compounds have a structural similarity with a class of bioactive oat compounds called avenanthramides. By developing a fermentation process for the engineered S. cerevisiae strain, we obtained a high‐yield production of Yav I and Yav II. To examine the biological relevance of these compounds, we tested their potential antioxidant and antiproliferative properties upon treatment of widely used cell models, including immortalized mouse embryonic fibroblast cell lines and HeLa cancer cells. The outcomes of our experiments showed that both Yav I and Yav II enter the cell and trigger a significant up‐regulation of master regulators of cell antioxidant responses, including the major antioxidant protein SOD2 and its transcriptional regulator FoxO1 as well as the down‐regulation of Cyclin D1. Intriguingly, these effects were also demonstrated in cellular models of the human genetic disease Cerebral Cavernous Malformation, suggesting that the novel phenolic compounds Yav I and Yav II are endowed with bioactive properties relevant to biomedical applications. Taken together, our data demonstrate the feasibility of biotechnological production of yeast avenanthramides and underline a biologically relevant antioxidant activity of these molecules. © 2015 BioFactors, 41(1):15–27, 2015